(untitled) (Journal of Hama University, 2022)
The present search aimed to determine the degree of need of teachers in the first episode of basic stage to training courses in the field of teaching methods, the search has been applied on a sample of (165) teacher in the first episode, and study the effect of gender, academic qualification and number of years of experience variables in the training needs, the search adopted the descriptive analytical method, for this purpose a questionnaire consisting of (25) item has been applied, results showed an arrangement of training needs perceptually important including choosing the appropriate teaching methods for students in the first place, there were statistically significant differences according to the gender for males , academic qualification for vacation students and number of years of experience for teachers with more than 10 years’ experience, in light of the results, the research presented some suggestions including the need for training courses to stem from the needs of teachers.